(untitled) (Nigerian Journal of Pharmaceutical Research, 2023)
Background: The influx of herbal drinks acclaimed to have aphrodisiac activities into the Nigerian society is rising daily but there is dearth of scientific information on the beneficial and adverse effects of these drinks in their consumers. Objectives: This study examined the usage and effects of aphrodisiac drinks on some human health parameters among commercial bus drivers in Ife-Central Local Government, Ile-Ife, Osun State, Nigeria. Methods: Two hundred commercial bus drivers were used for the study, selected through random sampling method. The drivers’ Body-Mass Indices (BMI), Blood Pressure (BP) and Random Blood Sugar (RBS) were measured through direct observation. Fifty samples of aphrodisiac drinks were purchased from a source in the open market. Results: From the data collected, 87.5% have used aphrodisiac drinks before (treatment group) while 12.5% have not used it before (control group). 44% use these drinks every day; 26.9% use every other day, 21.1% use occasionally, 4.0% use once a week, 1.7% use on weekend while 2.3% use the drinks rarely. The rate of consumption of the aphrodisiac drinks in simple mean scores (14.14) was above the average (high). Rate of use had no significant effect on the drivers’ BMI (t = -1.97, p > 0.05) but had significant effects on BP (t = 3.562, p < 0.05) and on RBS (t = 7.631, p < 0.05) respectively. Conclusion: Consumption rate of aphrodisiac drinks by the commercial bus drivers in Ile-Ife, Nigeria is high and the rate has significant effects on the drivers’ BP and RBS.